Feasibility of Auricular Acupressure as An Adjunct Treatment for Neonatal Opioid Withdrawal Syndrome (Nows). Issue 3 (July 2021) - Jackson, Heather J.; Lopez, Cristina; Miller, Sarah; Englehardt, Barbara
Background: The opioid epidemic in the United States continues to threaten public health. As a result of this crisis, neonatal opioid withdrawal syndrome (NOWS) has risen exponentially and requires a multitude of non-pharmacologic treatments to ensure healthy neonatal outcomes. Methods: This feasibility study implemented an acupressure protocol as informed by the Near-Term Infant (NTI) conceptual framework for the treatment of NOWS. Aims of this study were to assess provider training, effective integration of acupressure within the standard of care, and acceptance of this treatment by mothers and healthcare providers. Results: With maternal consent, a total of 12 participants were enrolled and underwent auricular acupressure. Nurse Practitioners were credentialed (75%) and effectively administered neonatal acupressure (100%) in accordance with the study protocol. Mothers were very satisfied with acupressure for the treatment of NOWS (Client Satisfaction Questionaire-8 mean scores 3.8–4.0 of a possible 4.0), and the majority of healthcare providers were supportive (66%, mean scores 3.6 to 4.0 out of possible 5). Conclusions: Auricular acupressure was successfully implemented within the standard of care for NOWS. Future studies should incorporate outlined suggestions and include qualitative measures of acceptance as well as randomized controlled trials to evaluate efficacy.